STUDENTS’ PERCEPTION IN USING DUOLINGO APPLICATION IN SPEAKING ACTIVITIES IN STATE JUNIOR HIGH SCHOOL 4 LANGGAM - Kurniawan, Robi; Buriyanti, Elgi (Indonesian Journal of Studies on Humanities, Social Sciences and Education, 2024)
This study explores the perceptions of students using the Duolingo application for speaking activities at State Junior High School 4 Langgam. The subject of this research is all eight students State Junior High School 4 Langgam. The data were collected through questionnaires. The questionnaire answers were analyzed descriptively using SPSS 21 and Microsoft Excel. Participants were instructed to select one Likert scale answer in each area based on the statement. By employing a quantitative descriptive method, the research aims to determine the effectiveness of Duolingo in enhancing speaking skills, based on students’ experiences and feedback. The results indicate a mixed perception among students, highlighting both the advantages and challenges of integrating Duolingo into the language learning curriculum.